Lack of recovery from radiation-induced sublethal damage in human haematopoietic cells. - Kimler, B. F. (Nature Publishing Group, 1984)
The effect of ionizing radiation on the growth of bone marrow cells from haematologically normal controls or from patients with acute nonlymphocytic leukaemia was studied using colony formation as an endpoint. A modified agar culture method which incorporated daily feeding with new medium was utilized to allow the growth of leukaemic cell colonies. Analysis of radiation-dose survival curves revealed that normal bone marrow cell populations exhibited a relatively steep slope, with values of D0 averaging 0.88 Gy, and essentially no shoulder to the survival curves. The leukaemic cells tested also displayed survival curves with negligible shoulders and steep slopes (average value of D0 = 0.66 Gy). The average values of D0 for normal and leukaemic cells were significantly different (P less than 0.001). The ability of hematopoietic progenitor cells to recover from the accumulation of sublethal damage was also investigated by allowing a fractionation interval between doses. As expected from the lack of significant shoulder on the survival curve, there was no evidence of recovery from sublethal damage. These results provide a rationale for the use of fractionated radiation therapy for whole-body irradiation prior to bone marrow transplant.